A new simplified mechanism for combustion of RP-3/Jet-A kerosene. Issue 6 (18th March 2020) - Chang, Liuyong; Lin, Yuzhen; Cao, Zhang; Xu, Lijun
ABSTRACT: Using a detailed mechanism to simulate complex combustion process is not practical at present, and simplified mechanisms must be developed. This study develops a simplified chemical reaction mechanism including 55 species and 202 reactions, applicable to a wide range of combustion regimes for RP-3/Jet-A kerosene. The simplified mechanism is validated by comparing with experimental data and the results predicted by detailed mechanism. The results predicted by the simplified mechanism conform well with that predicted by detailed mechanism and experimental data, indicating that the simplified mechanism can be employed to predict the experimental data of the RP-3 and Jet-A kerosene.